2013
DOI: 10.1088/0022-3727/46/17/175301
|View full text |Cite
|
Sign up to set email alerts
|

Structural and nanomechanical properties of InN films grown on Si(1 0 0) by femtosecond pulsed laser deposition

Abstract: The structural and nanomechanical properties of InN films grown on Si(1 0 0) using femtosecond pulsed laser deposition were studied for different growth conditions. Atomic nitrogen was generated by either thermal cracking or laser-induced breakdown (LIB) of ammonia. Optical emission spectroscopy was conducted on the laser plasma and used to observe atomic nitrogen formation. An indium buffer layer was initially grown on the Si substrate at low temperature. The surface structure and morphology were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Table II compares H NI and E c of InN films reported in the literature. [17][18][19][20][21][22] Results of the present research are intermediate among the scattered hardness and Young's moduli of InN films in a variety of thicknesses and growth surfaces by various growth methods. Results for H NI and E 1101 and E a using (1101) and (1120) faced InN films, respectively, are also included in the table, though such results seem to be rather preliminary since there is a scatter of H NI and E data values among the research groups.…”
Section: A Hardness and Young's Modulus Of Innmentioning
confidence: 54%
See 2 more Smart Citations
“…Table II compares H NI and E c of InN films reported in the literature. [17][18][19][20][21][22] Results of the present research are intermediate among the scattered hardness and Young's moduli of InN films in a variety of thicknesses and growth surfaces by various growth methods. Results for H NI and E 1101 and E a using (1101) and (1120) faced InN films, respectively, are also included in the table, though such results seem to be rather preliminary since there is a scatter of H NI and E data values among the research groups.…”
Section: A Hardness and Young's Modulus Of Innmentioning
confidence: 54%
“…Results for H NI and E 1101 and E a using (1101) and (1120) faced InN films, respectively, are also included in the table, though such results seem to be rather preliminary since there is a scatter of H NI and E data values among the research groups. 19,21 In general, H NI decreases in the order of the (0001), (1101), and (1120) surface in the wurtzite-structure semiconductors, whereas Young's modulus increases in the reverse order of the [0001], <1101>, and <1120> direction due to underlying dislocation motion at atomic or microscopic scale. 34 In thinner films, it may be difficult to evaluate correct elastic properties, which may easily lead to some variations of elastic properties.…”
Section: A Hardness and Young's Modulus Of Innmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoindentation technique is currently an effective method for probing mechanical features of thin films at nanoscale, without any concern about the limitation of sample size and shape [26]. However, it is noticed a large dispersion of the measured mechanical properties that were reported in literature [26][27][28]. This discrepancy is likely explained by the different growth methods used for InN epitaxy, the dissimilar growth conditions, the various InN thickness layers studied and the shape and indenter tip radius used in nanoindentation tests.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used to fabricate semipolar InN films, including radio-frequency plasma-assisted molecular beam epitaxy (RF-MBE), 16) metalorganic vapor phase epitaxy, 17) pulsed laser deposition, 18) and magnetron sputtering. 19) Although metal organic chemical-vapor deposition (MOCVD), and MBE have often been used in the growth of InN thin films, few studies have reported semipolar InN( 1013) grown directly on a LaAlO 3 substrate using RF-MOMBE.…”
Section: Introductionmentioning
confidence: 99%